Reclaiming conversation the power of talk in a digital age - Turkle, Sherry (Penguin Press, 2015)
"Preeminent author and researcher Sherry Turkle has been studying digital culture for over thirty years. Long an enthusiast for its possibilities, here she investigates a troubling consequence: at work, at home, in politics, and in love, we find ways around conversation, tempted by the possibilities of a text or an email in which we don't have to look, listen, or reveal ourselves. We develop a taste for what mere connection offers. The dinner table falls silent as children compete with phones for their parents' attention. Friends learn strategies to keep conversations going when only a few people are looking up from their phones. At work, we retreat to our screens although it is conversation at the water cooler that increases not only productivity but commitment to work. Online, we only want to share opinions that our followers will agree with - a politics that shies away from the real conflicts and solutions of the public square. The case for conversation begins with the necessary conversations of solitude and self-reflection. They are endangered: these days, always connected, we see loneliness as a problem that technology should solve. Afraid of being alone, we rely on other people to give us a sense of ourselves, and our capacity for empathy and relationship suffers. We see the costs of the flight from conversation everywhere: conversation is the cornerstone for democracy and in business it is good for the bottom line. In the private sphere, it builds empathy, friendship, love, learning, and productivity. But there is good news: we are resilient. Conversation cures. Based on five years of research and interviews in homes, schools, and the workplace, Turkle argues that we have come to a better understanding of where our technology can and cannot take us and that the time is right to reclaim conversation. The most human--and humanizing--thing that we do. The virtues of person-to-person conversation are timeless, and our most basic technology, talk, responds to our modern challenges. We have everything we need to start, we have each other"--